Therapeutic uses of platelet-rich plasma (PRP) in sport injuries – A narrative review - Prasad Patil; Mamtha Jadhav; Tarun Kumar Suvvari; Vimal Thomas (Journal of Orthopaedic Reports, 2024)
Introduction: Sports offer numerous health benefits, contributing to growth, development, physical fitness, and mental well-being. However, injuries are an inevitable part of sports, affecting both professional athletes and casual participants. The incidence of sports-related injuries has risen significantly due to increased participation, heightened competitiveness, inadequate injury prevention techniques, improper sporting gear, insufficient training, and overuse. Method: ology: A comprehensive literature search was performed in multiple databases such as PUBMED and SCOPUS. Relevant studies on therapeutic uses of platelet-rich plasma (PRP) in sports injuries were included. The findings provide a comprehensive overview of the topic. Results: Platelet-Rich Plasma (PRP) is a regenerative, minimally invasive, non-surgical procedure that accelerates healing by utilizing concentrated bioactive factors from the body. PRP has shown promising results in treating conditions such as patellar tendonitis, Achilles tendonitis, tennis elbow, partial rotator cuff tears, ligament tears, and mild to moderate arthritis. Following a PRP injection, athletes typically undergo a short period of rest from sports activities while attending rehabilitation therapy. This approach helps optimize healing and ensures an optimal outcome. Conclusion: PRP has shown great promise as a treatment modality for sports injuries. While further research is needed to optimize PRP protocols and understand its mechanisms of action in sports injuries, it holds significant potential for enhancing the recovery and rehabilitation of athletes, ultimately contributing to improved outcomes in the field of sports medicine.